31st AIAA Applied Aerodynamics Conference 2013
DOI: 10.2514/6.2013-2920
|View full text |Cite
|
Sign up to set email alerts
|

Over Wing Nacelle Installations for Improved Energy Efficiency

Abstract: Lockheed Martin (LM) has teamed with the Air Force Research Laboratory (AFRL) to evaluate over wing nacelle (OWN) configurations to better understand and exploit their potential performance characteristics for improving aircraft energy efficiency, threat avoidance, community noise abatement, and speed agility. This study represented a first-of-its kind detailed parametric study of OWN concepts using modern, high fidelity analysis and design processes to assess their feasibility for future mobility configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…Additionally, D i is the lift-induced drag of the airframe without propulsion system, and ∆D i is the change in lift-induced drag due to thrust, that is, the difference between the drag of the complete aircraft with the propulsor at a determined thrust setting, and the drag that would exist at T dp = 0 for the same total lift value. Although different drag breakdowns exist [30,36,37], this simplified approach has been selected because it clearly identifies the contribution of the installation effects. All lift and drag contributions can be expressed as non-dimensional coefficients by dividing them by the reference area of the wing S and the dynamic pressure of the freestream q ∞ .…”
Section: Thrust Lift and Drag Decompositionmentioning
confidence: 99%
“…Additionally, D i is the lift-induced drag of the airframe without propulsion system, and ∆D i is the change in lift-induced drag due to thrust, that is, the difference between the drag of the complete aircraft with the propulsor at a determined thrust setting, and the drag that would exist at T dp = 0 for the same total lift value. Although different drag breakdowns exist [30,36,37], this simplified approach has been selected because it clearly identifies the contribution of the installation effects. All lift and drag contributions can be expressed as non-dimensional coefficients by dividing them by the reference area of the wing S and the dynamic pressure of the freestream q ∞ .…”
Section: Thrust Lift and Drag Decompositionmentioning
confidence: 99%
“…The GasTurb results were loaded into the DMS via an interface program and were immediately available to all modules for application in the overall process. In addition to reducing the noise signature, the unconventional engine position behind the wing (see Figure 1) also improved the drag in cruise due to flow interactions between the wing and the propulsion unit, as shown in American studies by Hooker et al (2013). The investigations show a possible aircraft drag reduction of −5%.…”
Section: Preliminary Aircraft Designmentioning
confidence: 80%
“…They were obtained using a workstation running 12×2 GHz Intel Core i7 processors, which took approximately 1.5 min per flow and adjoint solution, respectively. Finally, the test problem was selected because it shared similarities with an OWN study previously reported, 24 and whose trends were later found to agree with a more advanced study by Hooker et al 25 A comparison of the test problem and the OWN problem is shown in Figs. 5 and 6.…”
Section: Test Problemmentioning
confidence: 92%